Kepemimpinan transformasional dan komunikasi organisasi: perannya terhadap kinerja karyawan - Choiriyah Choiriyah; Endah Andayani; Endi Sarwoko (MBR (Management and Business Review), 2020)
This study aims to investigate the effect of transformational leadership and organizational communication on employee performance achievement. Using a quantitative research approach, by collecting data from 120 employees as the research sample. The data analysis technique used Multiple Linear Regression analysis. The results showed that transformational leadership has a positive effect on employee performance, other findings indicate that organizational communication also has a positive effect on employee performance. Companies need to enhance transformational leadership and ensure that organizational communication is well-executed, clear and follows well-recognized channels. Future researchers could consider employee engagement variables as a mediator of the relationship between organizational communication and employee performance.